Determinants of tax avoidance: Related party transactions, foreign ownership, and tax disclosure - Nita Andriyani Budiman; Putri Bonita Handayani (Universitas Pendidikan Nasional, 2026)
This study aims to examine the effect of related party transactions, foreign ownership, and tax disclosure on tax avoidance in multinational companies listed on the Indonesia Stock Exchange. The study employs a quantitative approach using secondary data obtained from corporate financial statements and sustainability reports for the period 2018–2024. The sample was selected using a purposive sampling method, resulting in 98 firm-year observations that met the research criteria. Panel data regression was applied as the analytical method. The results indicate that related party transactions have a positive effect on tax avoidance, suggesting that the higher the intensity of transactions with related parties, the greater the tendency of firms to engage in tax avoidance practices. Foreign ownership is also found to have a positive effect on tax avoidance, indicating that firms with higher foreign ownership tend to implement more aggressive tax planning strategies. Meanwhile, tax disclosure has a negative effect on tax avoidance, implying that higher levels of tax transparency are associated with lower levels of tax avoidance. These findings suggest that related party transactions and foreign ownership increase the risk of tax avoidance, while tax disclosure plays an important role in mitigating such practices. This study contributes to the literature on corporate taxation and provides insights for policymakers in formulating regulations that enhance transparency and improve tax compliance among multinational companies in Indonesia. This study is particularly relevant in the context of Indonesia’s recent tax reforms, including the Harmonization of Tax Regulations Law, which emphasizes improved tax compliance, transparency, and the prevention of tax avoidance practices among corporate taxpayers.